2021
DOI: 10.1186/s12873-021-00422-6
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against medical advice from the emergency department in a university hospital

Abstract: Background Patients discharged against medical advice (DAMA) act as a high-risk population for the Emergency Department (ED), regardless of their presentations, and can pose a serious burden for the hospital. This study examines the prevalence, demographic and clinical characteristics, reasons, and clinical outcomes of a small sample of DAMA patients in a teaching university hospital, including readmission, morbidity, and mortality. Methods A prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…Previous studies have reported that ED intensity and prolonged ED dwell times increase the rate of DAMA. [ 18 , 19 ]. In our study, the total number of applications to the ED decreased compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ED intensity and prolonged ED dwell times increase the rate of DAMA. [ 18 , 19 ]. In our study, the total number of applications to the ED decreased compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 99%
“…Physician-specific factors include patient load at presentation time [ 35 ]—increasing number of patients also increasing admission, risk preference [ 36 , 37 ]—admission is more likely the more risk-adverse the physician is, and individual experience [ 32 ]. Patient-specific factors include living situation (e.g., children at home) [ 38 , 39 ], substance abuse [ 40 ]—patients are less likely to agree to admission, and established and well managed out-patient care or simply the patients [ 41 ] or proxies' preference [ 42 ]. Institutional factors include hospital capacity and inadequate out-patient care [ 34 ], necessitating inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…One of the explored content was dissatisfaction with the quality of medical care. This content is one of the most common and logical reasons for DAMA that have been mentioned in different fields of medicine [ 16 , 17 ]. The issue of dissatisfaction with the quality of treatment is not limited to DAMA.…”
Section: Discussionmentioning
confidence: 99%